Researcher perspectives on class size reduction. - Graue, Elizabeth; Rauscher, Erica (Education Policy Analysis Archives, 2009)
This article applies to class size research Grant and Graue’s (1999) position that reviews of research represent conversations in the academic community. By extending our understanding of the class size reduction conversation beyond published literature to the perspectives of researchers who have studied the topic, we create a review that includes political histories of, contextual details about, and assumptions undergirding the conversation. We find divergent (and sometimes competing) perspectives on identifying beneficiaries of class size reduction (or CSR) and the correct context in which to view CSR research. By contrasting the logic and assumptions embedded in pupil-teacher ratio (PTR), class size (CS), and class size reduction studies, we conclude that sometimes research conflates these constructs and their associated theories of action, and such distortion poorly serves the needs of policymakers and stakeholders in education. We recommend that future inquiry focus on mechanisms of change, particularly instruction—both in terms of instructional strategies that capitalize on the resource of a smaller group and the types of support needed for teacher and administrator professional development.